ISOLASI DAN IDENTIFIKASI BAKTERI ASAM LAKTAT (BAL) DARI BUAH MANGGA (Mangifera indica L.) - Arsyik Ibrahim; Aditya Fridayanti; Fila Delvia (Jurnal Ilmiah Manuntung, 2015)
The research has been done for the isolation and identification of lactic acid bacteria (LAB) from mango (Mangifera indica L.). This research aimed to isolated of lactic acid bacteria that is in mango (Mangifera indica L.) and determine the characteristics of lactic acid bacteria isolate (LAB) of mango (Mangifera indica L.). The method used is spoiled  technique of mango (Mangifera indica L.) and isolation using selective media MRS Broth and MRS Agar. The identification isolate of lactic acid bacteria (LAB) used methods macroscopically and microscopically with indirect coloring, gram staining and used biochemical with katalase testing. The results obtained in the form of characteristic isolate of lactic acid bacteria displayed form of bacteria with circle, smooth surface, curve, entire side and white. The microscopically displayed stick form of bacteria and purple with gram coloring